Perbedaan Motivasi dan Hasil Belajar Siswa SMKN 6 Jayapura Melalui Penerapan Model Pembelajaran Kumon - Rasyidi, Ahlan (UNIB Press, 2025)
This study aims to determine the differences in student motivation and learning outcomes after applying the kumon learning model with conventional learning models, using quantitative methods of quasi experimental design Nonequivalent Control Group model. The sampling technique used Purposive Sampling. Data collection by filling in questionnaires of learning motivation of experimental and control classes and learning outcomes tests of experimental and control classes. From the data analysis, the results of the motivation difference test were Sig. Hit = 0.039 < 0.05 and learning outcomes ranging from the results of n-Gain RPP 1 Sig. Hit = 0.040 < 0.05, n-Gain RPP 2 Sig. Hit = 0.041 < 0.05, n-Gain result of RPP 3 Sig. Hit = 0.046 < 0.05, and the average n-Gain result Sig. Hit = 0.029 < 0.05. The conclusion is that there are differences in student motivation and learning outcomes in classes applied to the kumon learning model with classes applied to conventional learning models and the kumon learning model can increase student motivation and learning outcomes.